Kinematic precise point positioning using GPS and GLONASS measurements in marine environments. (October 2017) - Alkan, Reha Metin; Saka, M. Halis; Ozulu, İ. Murat and İlçi, Veli
Highlights: The usability of Kinematic PPP with GPS-only and GPS&GLONASS is investigated. Kinematic PPP can potentially achieve cm to dm level accuracy. Combined GPS&GLONASS may provide continuous solution in limited satellite environment. Online GNSS processing services becomes strong alternative to conventional approach. Abstract: The Precise Point Positioning (PPP) technique has received increased attention in recent years. When employing PPP, users need only a single GNSS receiver data to obtain a cm to dm accuracy level on a global datum, both in static and kinematic modes. This technique has become more popular due to its easy use, simple field operations, no base station(s) requirement, and provides cost effective high accuracy positioning. In satellite-based positioning, the accuracy and reliability of the positioning results are strongly dependent on the number and geometry of visible satellites, and quality of the observations. This issue is more important when the measurements are conducted in environments where satellite signals are blocked or degraded in some places like narrow channels, ravines, congested harbors, coastal areas with intense urbanization, inland waterways, in waters having severe terrain obstructions or surrounded by high mountains. To overcome this limitation, a combination of GPS and GLONASS measurements are proposed, especially to achieve more reliable and accurate solutions by increasing the number of visible satellites. The additional satellite system's observations like GLONASS, are expected to enhance the positioning accuracy and solution availability where especially not enough numbers of GPS satellites are visible. As of today, precise orbits and clock data are available not only for GPS but also for GLONASS. This provides an opportunity to apply the PPP technique to GPS and GLONASS observations. In this study, performance of the PPP method is assessed in a dynamic environment using GPS-only and GPS + GLONASS observations. Accordingly, a kinematic test is carried out at the Obruk Lake Dam in the Çorum province, of Turkey. The collected data is processed using a globally popular on-line processing service: the Canadian Spatial Reference System-Precise Point Positioning Service (CSRS-PPP) operated by the Geodetic Survey Division of Natural Resources Canada (NRCan). The results show that the combined GPS + GLONASS data produced almost the same level of accuracy with the GPS-only data if there is a sufficient number of GPS satellites with good geometry. In the extreme cases, such as the elevation of satellites above 40 degrees, the GPS cannot provide a solution. However, when data and both satellites systems are combined, it is then possible to provide the solution. The results also reveal that a dm-level of accuracy can be achieved with the PPP technique in a dynamic environment. This accuracy level largely meets the requirements of many marine applications, including precise hydrographic surveying, marine geodesy, navigation and oceanography.